Improving betacyanins stability by sustainable application of xanthan gum, CMC and citric acid in fermented red dragon fruit drink: long-term storage, bio-accessibility and antioxidant activity - Lim, Teck Wei; Lim, Renee Lay Hong; Pui, Liew Phing; Tan, Chin Ping; Ho, Chun Wai (Institution of Chemical Engineers, 2025)
Red dragon fruit (Hylocereus polyrhizus) with high betacyanins content is a potential commercial fruit that can be developed into a functional drink. The development of a functional product not only requires innovation but also needs to consider the sustainability of the raw materials and techniques employed. The present study aimed to employ mild and sustainable approaches via the incorporation of xanthan gum (XG) and carboxymethyl cellulose (CMC) hydrocolloid mixture solution and citric acid (CA) at optimum concentrations to modify the matrix of fermented red dragon fruit drink (FRDFD) to produce Improved-FRDFD-dH2O with improved long-term storage stability, bio-accessibility and antioxidant activity of the betacyanins. Results revealed that 0.4 % XG and 0.5 % CMC hydrocolloid mixture solution was able to synergistically cooperate with 0.2 % CA for providing the best food matrix environment for the maximum betacyanins stability (<10 % degradation) throughout the 8-week storage period at 25°C. The simulated digestion study showed that the incorporation of 0.4 % XG and 0.5 % CMC hydrocolloid mixture solution and 0.2 % CA successfully improved the bio-accessibility (>80 % retained) and preserved the high antioxidant activities of betanin throughout the digestive process (up to 94.18 % free radicals inhibited).